PREMISES AND POTENTIAL FOR THE APPLICATION OF SEMIOTICS IN MARKETING RESEARCH - Magdalena Sobocińska (Acta Scientiarum Polonorum. Oeconomia, 2016)
Potential uses of semiotics in market research should be examined in the context of the multi-paradigmatic nature of marketing and the continuous development of qualitative research methods. The essence of semiotic approach is expressed in its focus on the contextual dimension of consumption. Semiotic studies represent a departure from the analytical examination of declarations, placing more emphasis on identification of behavioural changes and emerging trends in consumer attitudes. The semiotic approach places great significance on the analysis of cultural messages, also those propagated through mass media. Semiotic studies may be employed in brand management for portfolio-building, cultural branding and in the design of brand positioning strategies. It is also an effective instrument for the formulation of marketing messages and collation of cultural insights. To reduce the uncertainty of interpretation, results of semiotic analyses should be triangulated against those obtained using standard qualitative and quantitative methods.